Hubungan Kadar Serum Feritin Dengan Kejadian Stunting Pada Anak Talasemia β Mayor - Rita Agustina; Zulhafis Mandala; Rena Sahara (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Thalassemia is hemolytic anemia characterized by abnormalities in globin chain synthesis. Hemochromatosis and tissue hypoxia due to anemia are hormonal factors due to the accumulation of iron in the endocrine glands. Problems with endocrine glands and anemia can interfere with growth such as short posture. This study was to determine the correlation of serum ferritin levels with the incidence of stunting in beta-thalassemia major children in Abdul Moeloek Hospital in Lampung in 2019. This research uses an observational analytic method with a cross-sectional approach. The subjects in the study were 60 patients. The instrument used was medical record data. Statistical analysis using the Chi-Square test showed an association between ferritin levels and the incidence of Stunting in Thalassemia patients β Major children at Abdul Moeloek Hospital in Bandar Lampung in 2019 (p-value 0.018. OR 4.67). There is a relationship between ferritin levels with the incidence of Stunting in Thalassemia patients β Major children at Abdul Moeloek Hospital, Bandar Lampung in 2019.